The pliometrics exercises and your influence in the development of the explosive force in athletes of Handball (Review) (Revista científica Olimpia, 2019)
The development of explosive strength in sports handball constitutes a tremendous need so as to achieve the needs of modern game.In both sport disciplines the size of players has constituted a handicap so hard to overcome, so as to obtain a relevant result in the most important sport competitions of the national sport calendar. To overcome this handicap is only possible, acquiring significative levels in the development of explosive strength in the different muscular plans. Which has been stocked with the use of traditional methods to achieve the development of strength, using other ways to get that. From this point of departure we suggest to apply pliometrics exercises to develop muscles power, adapted to a group of 10 athletes of junior cathegory, female players of handball. The results of this team were prossed from the statistical point of view applying the correlation of Pearson (theory).
Keywords: plyometric exercises, muscular plane, development strong, explosive strong